Results of a sector-wide quality improvement initiative for substance-abuse care: an uncontrolled before-after study in Catalonia, Spain - Hilarion, Pilar; Groene, Oliver; Colom, Joan; Lopez, Rosa M; Suñol, Rosa (Substance abuse treatment, prevention and policy, 2010)
Background The Health Department of the Regional Government of Catalonia, Spain, issued a quality plan for substance abuse centers. The objective of this paper is to evaluate the impact of a multidimensional quality improvement initiative in the field of substance abuse care and to discuss potentials and limitations for further quality improvement. Methods The study uses an uncontrolled, sector-wide pre-post design. All centers providing services for persons with substance abuse issues in the Autonomous Community of Catalonia participated in this assessment. Measures of compliance were developed based on indicators reported in the literature and by broad stakeholder involvement. We compared pre-post differences in dimension-specific and overall compliance-scores using one-way ANOVA for repeated measures and the Friedman statistic. We described the spread of the data using the inter-quartile range and the Fligner-Killen statistic. Finally, we adjusted compliance scores for location and size using linear and logistic regression models. Results We performed a baseline and follow up assessment in 22 centers for substance abuse care and observed substantial and statistically significant improvements for overall compliance (pre: 60.9%; post: 79.1%) and for compliance in the dimensions 'care pathway' (pre: 66.5%; post: 83.5%) and 'organization and management' (pre: 50.5%; post: 77.2%). We observed improvements in the dimension 'environment and infrastructure' (pre: 81.8%; post: 95.5%) and in the dimension 'relations and user rights' (pre: 66.5%; post: 72.5%); however, these were not statistically significant. The regression analysis suggests that improvements in compliance are positively influenced by being located in the Barcelona region in case of the dimension 'relations and user rights'. Conclusion The positive results of this quality improvement initiative are possibly associated with the successful involvement of stakeholders, the consciously constructed feedback reports on individual and sector-wide performance and the support of evidence-based guidance wherever possible. Further research should address how contextual issues shape the uptake and effectiveness of quality improvement actions and how such quality improvements can be sustained.